Analysis of IMGSAC autism susceptibility loci: evidence for sex limited and parent of origin specific effects - Lamb, J (BMJ Group, 2005)
Background and methods: Autism is a severe neurodevelopmental disorder, which has a complex genetic predisposition. The ratio of males to females affected by autism is approximately 4:1, suggesting that sex specific factors are involved in its development. We reported previously the results of a genomewide screen for autism susceptibility loci in 83 affected sibling pairs (ASP), and follow up analysis in 152 ASP. Here, we report analysis of an expanded sample of 219 ASP, using sex and parent of origin linkage modelling at loci on chromosomes 2, 7, 9, 15, and 16. Results: The results suggest that linkage to chromosomes 7q and 16p is contributed largely by the male–male ASP (MLS = 2.55 v 0.12, and MLS = 2.48 v 0.00, for the 145 male–male and 74 male–female/female–female ASP on chromosomes 7 and 16 respectively). Conversely linkage to chromosome 15q appears to be attributable to the male–female/female–female ASP (MLS = 2.62 v 0.00, for non-male and male–male ASP respectively). On chromosomes 2 and 9, all ASP contribute to linkage. These data, supported by permutation, suggest a possible sex limited effect of susceptibility loci on chromosomes 7, 15, and 16. Parent of origin linkage modelling indicates two distinct regions of paternal and maternal identity by descent sharing on chromosome 7 (paternal MLS = 1.46 at ∼112 cM, and maternal MLS = 1.83 at ∼135 cM; corresponding maternal and paternal MLS = 0.53 and 0.28 respectively), and maternal specific sharing on chromosome 9 (maternal MLS = 1.99 at ∼30 cM; paternal MLS = 0.02). Conclusion: These data support the possibility of two discrete loci underlying linkage of autism to chromosome 7, and implicate possible parent of origin specific effects in the aetiology of autism.